Pengaruh Motivasi dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan pada PT. Samwon Copper Tube Indonesia - Bagas Prakoso; Liska Liska; Siti Zaitun Zunita (Yayasan Literasi Sains Indonesia, 2022)
In this study aims to determine how much influence the variables of motivation, work discipline on employee productivity at pt. samwon copper tube Indonesia. Where the variable used in this study is motivation which is indeed an impulse that arises in a person consciously or unconsciously to take an action with a specific purpose, with the variable employee work discipline in which a person can be organized, persistent and persistent. work in accordance with applicable rules by not violating the rules that have been set for the variable work productivity the ability to produce goods or services from various resources and capabilities possessed by each worker or employee with the results achieved by employees of PT Samwon Copper Tube Indonesia. As well as where this study used analytical techniques with the research method Classical Assumption Test, T Test, F Test and Coefficient of Determination Test by taking a random sample of 102 employees at PT Samwon Copper Tube and using quantitative data on the distribution of questionnaires to obtain research data results.